Business Development Strategy through Productive Waqf - Aqashah, Faisal; Siregar, Saparuddin; Yanti, Nursantri (Universitas Ibn Khladun Bogor, 2025)
This research discusses business development strategies through productive waqf with a case study at the Asy-Syafaah Mosque, Tebing Tinggi City. Productive waqf is an innovation in waqf asset management that aims to provide sustainable economic and social benefits. The Asy-Syafaah Mosque utilizes waqf assets in the form of kiosks that are rented out to the community, and the proceeds are used to finance the operation of a free afternoon madrasa for children. This research uses a qualitative approach with a field study method, including in-depth interviews, observation, and documentation. SWOT analysis is used to identify strengths, weaknesses, opportunities, and threats in productive waqf management based on kiosk leasing. The results showed that productive waqf management at the Asy-Syafaah Mosque is able to provide multiple benefits, namely supporting religious education and empowering the economy of the surrounding community. The right management strategy can be a reference for other mosques in developing productive waqf as an effort to empower the economy and social community.